AN EXPANDED CROSS-LINGUISTIC ANALYSIS OF EUPHEMISMS - Akramova Diyora Khaitbaevna (PEDAGOGS, 2025)
Annotation. This article expands on the cross-linguistic use of euphemisms. It surveys their functions, structural types, and cultural manifestations shortly across English, Chinese, Japanese, Arabic, Spanish, and Uzbek. The discussion demonstrates that while the impulse to euphemize is universal, the exact forms and cultural rationales are strikingly diverse.